2017
DOI: 10.1186/s12966-017-0599-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing group size of periodic in-person sessions in a remotely delivered weight loss intervention

Abstract: BackgroundFew randomized studies have examined differential effects of group size in behavioral weight control, especially in hybrid programs that include Internet treatment approaches.MethodsRandomized controlled trial (n = 195) comparing a 4 month hybrid internet weight loss program coupled with monthly face to face groups of 100 persons (Large Group, LG; 1 group) or to the same approach with monthly groups of 20 persons (Small Group, SG; 4 groups). Repeated-measures mixed-model analysis with age and race as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
(35 reference statements)
0
14
1
Order By: Relevance
“…The literature on effectiveness of remotely delivered approaches to treat obesity is promising, but the effects specific to minority populations are understudied. 64 A trial with predominantly Hispanic women participating in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) found that an internet-based weight loss program in addition to WIC resulted in significantly greater weight loss over 12 months compared with the WIC program alone. 63 Few studies had 50% or more participants from racial or ethnic minority groups or outcomes reported by race.…”
Section: Remotely Delivered Intervention Formatsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on effectiveness of remotely delivered approaches to treat obesity is promising, but the effects specific to minority populations are understudied. 64 A trial with predominantly Hispanic women participating in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) found that an internet-based weight loss program in addition to WIC resulted in significantly greater weight loss over 12 months compared with the WIC program alone. 63 Few studies had 50% or more participants from racial or ethnic minority groups or outcomes reported by race.…”
Section: Remotely Delivered Intervention Formatsmentioning
confidence: 99%
“…63 Subsequent studies have demonstrated the acceptability and feasibility of remotely delivered obesity programs and suggest strategies to enhance the recruitment of African Americans and Hispanics. 64 A trial with predominantly Hispanic women participating in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) found that an internet-based weight loss program in addition to WIC resulted in significantly greater weight loss over 12 months compared with the WIC program alone. 65 Intervening on neighborhood contexts Physical, or built, environments can profoundly shape health and health behaviors related to eating and physical activity.…”
Section: Community Health Worker Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4-month randomized controlled trial (N=195), fully described elsewhere and based on the Diabetes Prevention Program, provided data for this analysis. 9 Briefly, eligible partici-PA. Both groups received the same Internet components: weekly automated tailored feedback, self-monitoring tools (online or paper calorie tracking diary), tailored lessons and tools for problem-solving dietary and PA barriers, video resources, exercise planning tools (online scheduler and progression plan), and a message board for social support.…”
Section: Data Source and Study Designmentioning
confidence: 99%
“…Reasons for the weight loss disparity are not well understood. Mixed findings on racial differences in dietary and PA changes during BWI, 8,9 difficulty recruiting and retaining minorities, and a lack of conducting or reporting such analyses contribute to the knowledge gap. 7,10 More evidence is needed to understand and reduce the racial weight loss disparity.…”
Section: Introductionmentioning
confidence: 99%